The Young Elites - Lu, Marie, 1984- (G. P. Putnam's Sons, an imprint of Penguin Group (USA), 2014)
"Adelina Amouteru survived the blood fever, a deadly illness that killed many, but left others with strange markings and supernatural powers. Cast out by her family, Adelina joins the secret society of the Young Elites and discovers her own dangerous abilities"--